KEWENANGAN IDEAL MAHKAMAH PELAYARAN DALAM MENYELESAIKAN KECELAKAAN KAPAL UNTUK MEWUJUDKAN KEADILAN - Sarwono, Sarif; Ismail; Iryani, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The Shipping Court (Mahkamah Pelayaran) is a judicial body under the Ministry of Transportation (Kementerian Perhubungan) authorized to examine and rule on ship accidents, particularly concerning aspects of maritime safety and the responsibility of the shipmaster or officers, by issuing administrative sanctions. The regulations governing the function, authority, and duties of the Shipping Court are stipulated in Law Number 66 of 2024 concerning the third amendment to Law Number 17 of 2008, specifically in Articles 251 to 253 of the Shipping Law. Article 251 of the Shipping Law concerns the function of the Shipping Court; Article 252 concerns the authority to examine collisions between merchant ships, merchant ships and state-owned ships, and merchant ships and warships; and Article 253 outlines the duties of the Shipping Court, which include investigating the cause of a ship accident, determining the existence of procedural error or negligence on the part of the shipmaster or ship officer, examining the negligence of the operator, ship owner, or officers that led to the accident, and recommending administrative sanctions to the Minister. The method used in this research is normative legal research, conducted to obtain the necessary data related to the problem. The data utilized is secondary data, consisting of primary, secondary, and tertiary legal materials. Additionally, primary data is used to support the secondary data. Data analysis is performed using the qualitative juridical analysis method. The results of this study indicate that the current authority of the Shipping Court remains administrative and is not yet able to address the need for a more comprehensive sense of justice for victims, ship owners, or damaged third parties. This is significant because every ship accident involves not only technical navigation issues but also economic, environmental, and social losses. Although Law Number 66 of 2024 provides stronger administrative sanctions, it does not change the position of the Shipping Court as a quasi-judicial institution. Therefore, a restructuring of its authority toward a more integrative approach is needed so that the decisions of the Shipping Court can be recognized as part of the judicial process and serve as considerations for judges in the General Courts (Pengadilan Umum). This integrative process can be achieved by appointing the expert panel of the Shipping Court as ad hoc judges in the General Courts. This would allow the General Court's decisions to enhance and strengthen their quality through accurate and appropriate maritime technical considerations, given the expert panel's specialized background, experience, and expertise in shipping, thereby creating harmony between the decisions of the Shipping Court and the General Courts and reducing contradictions and strengthening legal certainty.